Randomised, controlled clinical trial evaluating the effects of preoperative insomnia treatment on postoperative pain control and recovery: a protocol for the Promoting Sleep to Alleviate Pain-Arthroplasty (PROSAP-A) trial - Martin Kraepelien; Michael R Irwin; Eva Kosek; Michael T Smith; Martin F Bjurström; Kristoffer Bothelius; Pernilla Maathz; Susanna Jernelöv; Alexander H C Rosenström; Andrea Niklasson; Richard Olmstead; Patrick H Finan (BMJ Open)
Introduction Sleep is a biological necessity with vital effects on all tissues and organs of the body. Preoperative sleep disturbance is associated with increased postoperative pain intensity and opioid consumption. Given that insomnia is a potentially modifiable risk factor, interventions targeting sleep prior to surgery may improve postoperative pain control and enhance key outcomes of recovery.Methods and analysis Promoting Sleep to Alleviate Pain-Arthroplasty (PROSAP-A) is a randomised, parallel group, two arm, controlled trial evaluating the effects of preoperative sleep-promotion on postoperative pain control, brain health and physical recovery. The main objective is to investigate whether preoperative insomnia treatment in patients scheduled to undergo total knee arthroplasty (TKA) or total hip arthroplasty (THA) may improve acute postoperative pain control. 100 adults with insomnia disorder (Insomnia Severity Index score >10 and confirmed Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition criteria for persistent insomnia disorder), scheduled to undergo primary TKA or THA, will be randomised to preoperative cognitive behavioural therapy for insomnia (CBT-I) or an active comparator control intervention, sleep education therapy (SET). Both interventions will be delivered over 4 weeks in hybrid format through a digital self-guided platform in combination with weekly telehealth video sessions with a psychologist (CBT-I) or research nurse (SET). A video-assisted booster session will be provided 1–2 weeks postoperatively. The primary outcome measure is acute postoperative pain intensity, averaged over the first 7 postoperative days (POD). Secondary outcome measures include long-term postoperative pain control, changes in quantitative sensory testing variables (eg, temporal summation, conditioned pain modulation), sleep, cognition (eg, attention, memory, processing speed, executive function), mental health, health-related function, physical activity, quality of life and blood biomarkers. Participants will undergo on-site evaluation preoperative (preintervention and postintervention) and 6 months postoperative. Additional remote assessments will take place during POD1–7, 3 and 12 months postoperative.Ethics and dissemination The Swedish Ethical Review Authority has approved the PROSAP-A trial protocol. Results will be published in international peer-reviewed journals and summaries will be provided to funders and participants of the trial.Trial registration number NCT06145516.